2021
DOI: 10.1149/2162-8777/abf47e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Pad Surface Roughness of Diamond Conditioning Process for CMP

Abstract: Chemical Mechanical Polishing/Planarization (CMP) is the key process of the wafer and thin film planarization process for semiconductor manufacturing. In the CMP process, the pad can restore its surface topography and efficiency by diamond conditioner or named as diamond conditioning process. The pad surface roughness is essential to the removal rate in the CMP process because it can represent the contact level of the polishing pad and wafer. This study has developed a simulation program based on precise diamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Pham [17] verified that the roughness of the polishing pad will be greater where the grain trajectories overlap, and divided the polishing pad into multiple concentric circles, and compared the number of track coincidence points in each concentric circle to predict the polishing pad roughness distribution. Li [18] found that the intersection density of grain tracks affects the pad roughness, and the pad roughness becomes stable only when the track overlap density reaches a certain amount. Eungchul [19] conducted a topological analysis of the dressing process in CMP to calculate the amount of polishing pad wear caused by the movement of grains, the wear depth of the polishing pad was analyzed under the condition of equal pressure, and the dressing effect of the polishing pad was obtained by simulating the dressing process.…”
Section: Introductionmentioning
confidence: 99%
“…Pham [17] verified that the roughness of the polishing pad will be greater where the grain trajectories overlap, and divided the polishing pad into multiple concentric circles, and compared the number of track coincidence points in each concentric circle to predict the polishing pad roughness distribution. Li [18] found that the intersection density of grain tracks affects the pad roughness, and the pad roughness becomes stable only when the track overlap density reaches a certain amount. Eungchul [19] conducted a topological analysis of the dressing process in CMP to calculate the amount of polishing pad wear caused by the movement of grains, the wear depth of the polishing pad was analyzed under the condition of equal pressure, and the dressing effect of the polishing pad was obtained by simulating the dressing process.…”
Section: Introductionmentioning
confidence: 99%